Design Factors that Reduce the Incidence of Elderly Falls in Nursing Homes (A Case Study of Nursing Homes for the Elderly in Lattakia City( - خضرة سجا; رنا بدر (Latakia University Journal -Engineering Sciences Series, 2023)
Achieving safety and security for the elderly is one of the basic principles of nursing homes design, and safety is related to identifying, controlling and preventing risks. There are many potential safety challenges, which need to be highlighted and appropriate solutions and treatments provided to avoid their risks. But the fall of the elderly is one of the most important risks in nursing homes, which poses a major design challenge for care homes, especially since the elderly suffer from weakness in functional abilities in general, and mobility abilities in particular, and here the surrounding built environment plays a role, which may be positive. By supporting their abilities and compensating for the deficiency in them, or negatively by thwarting the remaining capabilities they have, which is reflected in the frequent falls, which the elderly is exposed to and that cause them harm in various forms, as a result of the failure of the architectural design to support their abilities and potentials. The research presents an analytical study of some nursing homes in the city of Lattakia with the aim of verifying the extent to which the internal built environment achieves safety and security, and reduces the incidence of falls that the elderly may be exposed to, and evaluate them according to the recommended standards. It was found that the design of the studied care homes did not take into account most of the principles and standards recommended to reduce the incidence of falls. Thus, the research provides evidence and design guidelines to reduce the incidence of falls in nursing homes.